Quantitative evaluation on indigent criminal defense funding - McKinney, Ralph E. (2009)
This article takes a quantitative approach to build upon McKinney and Shao's (2008) qualitative contribution concerning resource a/location of indigent criminal defense programs. By compating public funds of multiple societies over time, we are able to add important knowledge surrounding property rights valuations using a new concept called GDP Indexed Purchasing Power Parity. The findings of this study show that GDP-PPP provides for better indigent criminal defense analysis than per capita figures